Effects of aging and long‐term physical activity on mitochondrial physiology and redox state of the cortex and cerebellum of female rats. Issue 24 (21st December 2022) - Mesquita, Paulo H. C.; Osburn, Shelby C.; Godwin, Joshua S.; Roberts, Michael D.; Kavazis, Andreas N.
Abstract: We investigated the effects of aging and long‐term physical activity on markers of mitochondrial function and dynamics in the cortex and cerebellum of female rats. Additionally, we interrogated markers of oxidative damage and antioxidants. Thirty‐four female Lewis rats were separated into three groups. A young group (YNG, n  = 10) was euthanized at 6 months of age. Two other groups were aged to 15 months and included a physical activity group (MA‐PA, n  = 12) and a sedentary group (MA‐SED, n  = 12). There were no age effects for any of the variables investigated, except for SOD2 protein levels in the cortex (+6.5%, p  = 0.012). Long‐term physical activity increased mitochondrial complex IV activity in the cortex compared to YNG (+85%, p  = 0.016) and MA‐SED (+82%, p  = 0.023) and decreased carbonyl levels in the cortex compared to YNG (−12.49%, p  = 0.034). Our results suggest that the mitochondrial network and redox state of the brain of females may be more resilient to the aging process than initially thought. Further, voluntary wheel running had minimal beneficial effects on brain markers of oxidative damage and mitochondrial physiology. Abstract : There were minimal changes in several markers of mitochondrial content, function, and dynamics in the cortex and cerebellum of female rats in response to both aging and long‐term physical activity. The brain mitochondrial physiology and redox homeostasis of females may be more resilient to the aging process than initially thought.